2016
DOI: 10.1002/stem.2467
|View full text |Cite
|
Sign up to set email alerts
|

Karyopherin Alpha 1 Regulates Satellite Cell Proliferation and Survival by Modulating Nuclear Import

Abstract: Satellite cells are stem cells with an essential role in skeletal muscle repair. Precise regulation of gene expression is critical for proper satellite cell quiescence, proliferation, differentiation and self -renewal. Nuclear proteins required for gene expression are dependent on the nucleocytoplasmic transport machinery to access to nucleus, however little is known about regulation of nuclear transport in satellite cells. The best characterized nuclear import pathway is classical nuclear import which depends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“… 81 ) Analysis of KPNA1 knockout mice further revealed that KPNA1 is important for muscle regeneration. 83 ) That is, KPNA1 knockout caused muscle satellite cells to prematurely activate and undergo apoptosis, which led to the exhaustion of muscle satellite cells. On the other hand, knocking out KPNA7 results in reduced reproductivity and fetal lethality in females.…”
Section: Lessons From Studies Of Importin αmentioning
confidence: 99%
“… 81 ) Analysis of KPNA1 knockout mice further revealed that KPNA1 is important for muscle regeneration. 83 ) That is, KPNA1 knockout caused muscle satellite cells to prematurely activate and undergo apoptosis, which led to the exhaustion of muscle satellite cells. On the other hand, knocking out KPNA7 results in reduced reproductivity and fetal lethality in females.…”
Section: Lessons From Studies Of Importin αmentioning
confidence: 99%
“…Mononucleated cells were isolated from muscles and labeled with antibodies against Annexin V and PI to detect apoptotic cells (Fig. 3D), a method previously shown to correlate well with caspase 3 analyses of apoptotic SC in histologic sections (10). The percentage of early apoptotic (Annexin V ϩ /PI Ϫ ) tdTomato ϩ Vcam1 Ϫ/Ϫ SC was approximately twofold higher than Vcam1 ϩ/ϩ (Fig.…”
Section: Vcam-1 Deficiency Alters Sc Lineage Progression and Survival But Not Self-renewal During Regenerationmentioning
confidence: 81%
“…To analyze in vivo satellite cell apoptosis, isolated mononucleated cells from hindlimb muscle were labeled with propidium iodide (PI) and 1:40 Annexin V-FITC (Biolegend) in 10 mM HEPES, 140 mM NaCl, and 2.5 mM CaCl2 (pH 7.4) (10). Apoptotic cells were defined as Annexin V ϩ /PI Ϫ from the tdTomato ϩ satellite cell population (10).…”
Section: Methodsmentioning
confidence: 99%
“…Cells with depleted importin α5 exhibit premature activation and proliferation, leading to exhaustion and cell death. Moreover, critical protein cargoes are disrupted because of the impaired localization of importin α5 (Choo et al, 2016). FIGURE 2 | Model of nuclear import and export.…”
Section: Role Of Importins In Cell Differentiationmentioning
confidence: 99%